Pengaruh Model Pembelajaran Kooperatif Tipe STAD Terhadap Keaktifan Belajar Siswa Kelas 2 SDN Morkoneng 1 - Achmad Noval Abrori; Conny Dian Sumadi (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
The purpose of this study was to determine the effect of the Student Teams Achievement Division (STAD) type of cooperative learning model on the learning activity of Class II students at SDN Morkoneng1. This research is an experimental research using the research design Nonequivalent Control Group Design. Sampling by Sampling Porporsive sampling type. The research sample was 40 students, namely 20 students in class IIA and 20 students in class IIB. Data was collected using observation sheets. The results showed that the cooperative learning model of the Student Teams Achievement Division (STAD) type had an effect on student learning activity. The magnitude of the effect is evident from the comparative t-test of two independent samples. The results of the comparative t-test calculation of two independent samples obtained a significance value of 0.000. Based on the test criteria if the value of Sig. (2-tailed) < 0.05 (0.000 < 0.05) then H0 is rejected and Ha is accepted, which means that there is an influence on the application of the cooperative learning model type Student Teams Achievement Division (STAD) on the learning activity of Class II students at SDN Morkoneng1. STAD Learning Model, Learning Activeness, Student.